Benefits of Diabetes Support Group in Chronic Disease Management Program (Prolanis) in Puskesmas Jetis II, Bantul District: a Case Study - Yulia Dewi Irawati; Adi Heru Sutomo; Mora Claramita (Faculty of Medicine, Public Health, and Nursing, 2019)
Background: Type 2 diabetes mellitus is a chronic disease and has the potential for complications that affect the entire body so that it requires a comprehensive approach. This means that the management of DMT2 must involve various parties, both medical, paramedic, patient, family and community. One strategy for managing DMT2 is Prolanis (Chronic Disease Management Program) which is a diabetes support group at Jetis II Health Center. To find out the success of Prolanis implementation, an evaluation of the benefits of the diabetes support group is needed.Objective: To find out the benefits obtained from participating in the diabetes support group in Prolanis at the Jetis II Bantul Health Center.Method: A qualitative descriptive study with a case study approach. Data were obtained from patients with DMT2 members of Prolanis (Chronic Disease Management Program) and officers of the Jetis II health center in Bantul Regency. Retrieval of data in patients with focus group discussions on 30 resource persons divided into 3 groups. Other data is by conducting independent interviews with 6 informants of the puskesmas staff involved in the diabetes support group activities of Prolanis.Results: The benefits obtained from the diabetes support group are grouped into 3 categories namely biopsychosocial support, information, and individual empowerment. Most patients benefit from obtaining biopsychosocial support from the Prolanis group. Benefits for DMT2 patients Prolanis members get information in the second place and the last is individual empowerment at least the benefits are felt.Conclusion: The benefits of a diabetes support group for DMT2 patients in Prolanis members are to get biopsychosocial support, information, and individual empowerment.